Ketetapan Dan Integritas Seorang Hamba Tuhan Di Tengah-Tengah Masyarakat Majemuk (Jurnal Pendidikan Agama dan Teologi, 2023)
Integrity is a condition in which a servant of God can be trusted because the words issued and actions are similar. The integrity of a servant of God must be seen in his life of service and personal life because both of these will have an impact on eternity, namely eternal salvation. As a very young shepherd, the apostle Paul gave several pieces of advice so that he could become a servant of God with integrity. To become a servant of God with integrity, there are several pieces of advice that must be followed regarding public life. and personal life. Three things that  the main things that Timothy had to do with regard to public life were to provide sound teaching, maintain respect and have a balance in service. The congregation will still have respect  if  Timothy has always been an example to the congregation in words, behavior, love, faith and purity or holiness of life. Furthermore, what is meant by balance in ministry is that Timothy remains diligent in reading God's Word, giving advice and teaching God's Word. In relation to his personality, Timothy had to use the gifts that God had given him. In addition, have a commitment to be obedient to do everything that the Apostle Paul has taught. As a result of doing these things, Timothy will save himself and every church he serves.